A definição da competência para o processo e julgamento dos crimes praticados por organizações criminosas - Baldresca, Raecler (2016)
This thesis starts from of the influence of the phenomenon of globalization on organized crime, examines the characteristics, structural models and forms of action of these delinquent groups in Brazil and abroad, and affirms the need for a differentiated treatment to control their activities. The work argues that the methods of investigation and proceeding individual crime − created to front the individual crime that offends only an individual legal interest in a particular location − are insufficient to treat the multi-subjective crime today, requiring the examination of its entire length and not in a fragmented way. From these bases and the analysis of the traditional criteria fixing the competence focused on individual crime, it says that there are rules in the Brazilian legal system which constitute a different criminal procedural system, which provides special investigation tools and requires the jurisdiction for proceeding and judge of crimes committed by criminal organizations to be set considering the peculiarities of this delinquent species